Was size of healthcare institution a factor affecting changes in healthcare utilisation during the COVID-19 pandemic in Korea? A retrospective study design analysing national healthcare big data - Chris Lane; Hyun-Ji Lee; Young-Taek Park; Jinhyung Lee (BMJ Open)
Objectives Many small-sized healthcare institutions play a critical role in communities by preventing infectious diseases. This study examines how they have been impacted by the global COVID-19 pandemic compared with large hospitals.Design This study adopted a retrospective study design looking back at the healthcare utilisation of medical facilities according to size after the COVID-19 pandemic. The dependent variable was change in the number of outpatient health insurance claims before and after onset of the COVID-19 pandemic. The independent variable was an observation time point of the year 2020 compared with 2019.Setting and participants The study was conducted in Korea having a competitive medical provision environment under the national health insurance system. The units of analysis are hospitals and clinics: tertiary hospitals (42), general hospitals (293), small hospitals (1272) and medical clinics (27 049). This study analysed all the health insurance claim data from 1 January 2019 to 31 December 2020.Results Compared with 2019, in 2020, there were significant decreases in the number of claims (−14.9%), particularly in small hospitals (−16.8%) and clinics (−16.3%), with smaller decreases in general hospitals (−8.9%) and tertiary hospitals (−5.3%). The reduction in healthcare utilisation increased as the size of institutions decreased. The magnitude of decrease was significantly greatest in small hospitals (absolute risk (AR): 0.8317, 0.7758 to 0.8915, p<0.0001; relative risk (RR): 0.8299, 0.7750 to 0.888, p<0.0001) followed by clinics (AR: 0.8369, 0.8262 to 0.8478, p<0.0001; RR: 0.8362, 0.8255 to 0.8470, p<0.0001) even after controlling institutional covariates.Conclusion The external impact of the pandemic increased incrementally as the size of healthcare institutions decreased. Healthcare policy-makers need to keep in mind the possibility that small hospitals and clinics may experience reduced healthcare utilisation in the infectious disease pandemic. This fact has political implications for how healthcare policy-makers should prepare for the next infectious disease pandemic.